Bahasa Inggris - Thiara Adzkia Muthmainnah; Syamsiah; Andi Mu’nisa; Firdaus Daud; Faisal (Jurnal Penelitian Pendidikan IPA, 2026)
This quasi-experimental study employed a pretest–posttest control group design to examine the effect of Collaborative Mind Mapping in Inquiry-Based Learning on students’ collaboration skills and learning outcomes in biology Grade XI at SMA Negeri 3 Enrekang. The population comprised 105 Grade XI FA students. Two class (XI FA 1 and XI FA 2; n = 70) were selected using cluster random sampling, with one class assigned as the experimental group and the other as the control group. Data were collected using a collaboration skills observation sheet developed based on the indicators and rubrics proposed by Greenstein (2012) and the administration of pretest and posttest learning outcome questions. Descriptive analysis showed that the experimental group’s mean collaboration score increased from 40.36 to 78.93, higher than the control group (39.23 to 68.04). Similarly, learning outcomes improved from 58.51 to 86.49 in the experimental group, compared to 58.40 to 75.20 in the control group. The ANCOVA analysis results obtained a significance value for collaboration skills of 0.000 < 0.05, and a significance value for learning outcomes of 0.002 < 0.05. It can be concluded Collaborative Mind Mapping in inquiry-based learning significantly improves students' collaboration skills and learning outcomes in biology Grade XI.